Some Opinions on Copyright in the People’s Republic of China - Shoukang, Guo (Columbia Journal of Asian Law, 1987)
This comment will provide my personal observations on the likely content of the law on copyrights that China intends to promul- gate. My observations represent only my own opinions and should not be taken as Chinese government policy. The Chinese government established a State Copyright Bureau (Guojia Banquan Ju) in 1985. One of its senior officials formally declared at that time that it would be “not long” before the copyright law was promulgated. After the copyright law is promulgated, China will join one or more of the international copyright organizations as soon as the conditions are ripe.